In-vitro Assessment of Silver Diamine Fluoride Effect on Natural Carious Dentin Microhardness - Prakash, Meghna; Kang, Yoon H.; Jain, Shruti; Zandona, Andrea Ferreira (Frontiers in Dental Medicine, 2021)
This study aimed to assess the effect of silver diamine fluoride (SDF) on natural carious dentin microhardness and the correlation between tactile sensation, fluorescence, and microhardness on carious dentin. Permanent carious teeth scored ICDAS 4–6 were longitudinally sectioned into tooth slabs exposing carious dentin on one side and sound dentin on the other. Both sides were assessed for tactile sensation (soft/leathery/firm), fluorescence (red/pink/no fluorescence) with FACE technology (SiroInspect®, Dentsply Sirona, USA), and Vickers's microhardness (VMH). Samples were randomized into 3 groups based on SDF protocol (n = 30): Control/Group A- No SDF treatment; Group B- 38% SDF (Advantage Arrest™, Elevate Oral Care®, USA); Group C- SDF with potassium iodide/KI (Riva Star, SDI, Australia). After SDF application, all samples were stored for 1 week under 100% humidity at 37°C and re-assessed for tactile sensation, fluorescence, and microhardness. Change in microhardness (ΔVMH; mean ± SD), tactile sensation (ΔT), and fluorescence (ΔF) were calculated using the difference between pre-SDF and post-SDF values. Mixed ANOVA analysis showed that ΔVMH of carious and sound surfaces were statistically significantly higher for each of the experimental groups (Group B-sound: 20.22 ± 11.98 HV, carious: 19.76 ± 9.35 HV; Group C-sound: 14.26 ± 10.11 HV, carious: 22.51 ± 7.67 HV) than the control group (Group A–sound: 7.34 ± 8.28 HV, carious: 0.69 ± 3.53 HV) (p < 0.0001). There was no statistically significant difference between the experimental groups themselves for carious surfaces (p = 0.146). On sound surfaces, Group B showed a statistically significantly higher ΔVMH than Group C (p = 0.026). There was no statistically significant interaction between type of surface and ΔVMH in Group B (p = 0.809). In Group C, sound surfaces showed a statistically significantly lower ΔVMH than carious surfaces (p < 0.0001). Spearman rank-order correlation showed a statistically significant negative correlation between ΔVMH and ΔT (rs = −0.588, p < 0.0001) and between ΔVMH and ΔF (rs = −0.269, p = 0.01). There was a statistically significant positive correlation between ΔT and ΔF (rs = 0.226, p = 0.032). In conclusion, the microhardness of SDF-treated dentin surfaces increased as compared to non-SDF-treated surfaces. SDF (Advantage Arrest™) increased microhardness of carious and sound dentin to a similar extent whereas, SDF/KI (Riva Star) increased microhardness of carious dentin more than sound dentin. An increase in microhardness was correlated with a firmer tactile sensation.